contrasts of the south - Grigoryeva, Elena; Lidin, Konstantin (project baikal, 2024)
We, the inhabitants of the Northern Hemisphere, first of all associate the South with a hot climate. The small region of tropical and subtropical Asia is home to three quarters of the world’s population and an amazing diversity of cultures, lifestyles and traditions. In this issue we focus on Jordan, Armenia, Uzbekistan, Kazakhstan and the south of eastern Russia – Transbaikalia and Primorye. The cultural heritage of the South is only beginning to be recognized as a value, as an asset of all mankind, and as an inexhaustible storehouse of ideas relevant both today and tomorrow.